일부 임상치과위생사의 치과보철물 제작 과정에서의 감염관리에 대한 교육경험, 인식 및 실천도 - 박경화; Kyung-hwa Park; 최혜정; Hye-jung Choi (Han'guk Ch'iwisaeng Hakhoe chi, 2017)
Objectives: The purpose of this study is to investigate the relationship between education experience, awareness and practice of infection control during the prosthodontic treatment in clinical dental hygienists. Methods: A self-reported questionnaire was answered by 255 clinical dental hygienists in Seoul and Gyeonggi areas from October 10 to December 30, 2016. The questionnaire consisted of general characteristics of the subjects (8 items), dental prosthesis infection education experience (5 items), dental prosthesis infection awareness (5 items) and dental prosthesis infection practice (14 items) based on Likert 5 point scale. For statistical analysis, SPSS Statistic 22.0 was used. Results: A significant association was shown among education experience, awareness and practice of infection control during the prosthodontic treatment of clinical dental hygienists (p<0.001). Dental hygienists count, dental prosthesis infection education experience and awareness had positive influences, but the age group from 26 to 30 had negative influence on dental prosthesis infection practice. Conclusions: The study confimed that the dental prosthesis infection education program and continued education is necessary for the safety and health of patients, and to prevent the cross-infections of the clinical dental hygienists.